Online viewers' choices over advertisement number and duration. Issue 2 (22nd May 2020) - Nettelhorst, Stephen; Brannon, Laura; Rose, Angela; Whitaker, Whitney
Abstract : Purpose: The purpose of this study is to investigate online viewers' preferences concerning the number and duration of video advertisements to watch during commercial breaks. The goal of the investigations was to assess whether online viewers preferred watching a fewer number of advertisements with longer durations or a greater number of advertisements with shorter durations. Design/methodology/approach: Two studies used experimental research designs to assess viewers' preferences regarding advertisements. These designs used two independent variables and one dependent variable. The first independent variable manipulated the type of choice options given to online viewers (e.g. one 60 s or two 30 s advertisements). The second independent variable manipulated when the choice was given to online viewers (i.e. at the beginning of the viewing experience or in the middle of the experience). The dependent variable measured viewers' choices concerning their preferred advertisement option. Findings: The results across both studies found that participants made choices that minimized total advertisement exposure time when possible. When minimizing total exposure time was not possible, participants made choices that minimized the number of exposures instead. Originality/value: These investigations extend the literature on advertisement choice by examining online viewers' preferences about the format of their advertising experience rather than the content of the persuasive messages themselves. In addition, these investigations provide value by investigating viewers' responses to stimuli within realistic online simulations rather than abstract hypotheticals.